Diet, life-style and the prevalence of obesity and hypertension among Zulu women in a remote rural area - De Villiers, Maria Aletta (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Nutrition) -- University of Stellenbosch, 1988.